Operation monitoring platform of relay protection equipment at distribution network side under the background of new power system - Qingsheng Li; Yu Zhang; Zhaofeng Zhang; Zhen Li (Energy Informatics)
Abstract The new power system puts forward higher requirements for the functionality, real-time performance and reliability of relay protection equipment. Therefore, this paper designs a monitoring platform for the operation of relay protection equipment at distribution network side under the background of new power system. The platform obtains the running state of relay protection equipment by establishing simulation models of different types of relay protection equipment on the distribution network side. The fault time, fault type and current action of relay protection equipment at distribution network side are analyzed to realize the monitoring of operation state. At the same time, the visual representation method of monitoring data based on three-dimensional parallel scattergram and human-computer interaction is adopted for human-computer interaction, and the electromechanical protection device is controlled to realize current quick-break protection and overcurrent protection. The experimental results show that the platform can effectively monitor the operation of relay protection equipment on the distribution network side in real time and accurately judge the action of the equipment, and the application effect is good.